Molecular Bases of VEGFR-2-Mediated Physiological Function and Pathological Role - Wang, Xinrong; Bove, Alfredo Maria; Simone, Giuseppe; Ma, Binyun (Frontiers in Cell and Developmental Biology, 2020)
The VEGF/VEGFR-2 system participates in vasculogenesi and angiogenesis. Angiogenesis, as an important mechanism in many physiological and pathological processes, is involved in endothelial cell proliferation, migration, and survival, and leads to further tubulogenesis, and finally promotes formation of vessels. This series of signaling cascade pathways are precisely mediated by VEGF/VEGFR-2 system. The VEGF binding to the IgD2 and IgD3 of VEGFR-2 induces the dimerization of the receptor, subsequently the activation and trans-autophosphorylation of the tyrosine kinase, and then the initiation of the intracellular signaling cascades, finally the VEGF-activated VEGFR-2 stimulates and mediates variety of signaling transduction, biological responses, and pathological processes in angiogenesis, in which several crucial phosphorylated sites Tyr801, Try951, Try1175, and Try1214 in the VEGFR-2 intracellular domains mediate several key signaling processes including PLCγ-PKC, TSAd-Src-PI3K-Akt, SHB-FAK-paxillin, SHB-PI3K-Akt, and NCK-p38-MAPKAPK2/3 pathways. Based on the molecular structure and signaling pathways of VEGFR-2, the strategy of the VEGFR-2-targeted therapy should be considered to employ in the treatment of this system-associated diseases by blocking the VEGF/VEGFR-2 signaling pathway, inhibiting VEGF and VEGFR-2 gene expression, blocking the binding of VEGF and VEGFR-2, and destroying vascular endothelial cells expressing VEGFR-2.